CPA Examination: Accounting Practice. - Chamberlain, John H. (The Accounting Review, 1965)
The article presents various accounting problems prepared by the Board of Examiners of the American Institute of Certified Public Accountants. These problems were presented as the second half of the Certified Public Accountant examination in accounting practice on November 5, 1964. The candidates were required to solve problems one through four and either five or six in limited time. One series of questions pertains to John Brown, who is employed by Clairemont Manufacturing Corp. as a salesman, and his wife Irma. John Brown is also the proprietor of Brown Manufacturing Co. which employs two people and employs his wife as bookkeeper. Another series of questions relates to three attorneys who agreed to consolidate their individual practices as of January 1, 1963.